Congestive hepatopathy: Differentiating congestion from fibrosis. Issue 6 (2nd January 2018) - Lemmer, Alexander; VanWagner, Lisa; Ganger, Daniel
Abstract : Watch a video presentation of this article Watch the interview with the author